Low dose of Juçara pulp (Euterpe edulis Mart.) minimizes the colon inflammatory milieu promoted by hypercaloric and hyperlipidic diet in mice. (February 2021) - Silva, F.P.; De Miranda, D.A.; Carnier, M.; Maza, P.K.; Boldarine, V.T.; Silva Rischiteli, A.B.; Avila, F.; Pontes, L.P.P.; Hachul, A.C.L.; Neto, N.I.P.; Ribeiro, E.B.; Oller do Nascimento, C.M.; et al.
Graphical abstract: Highlights: Juçara supplementation decreased the pro-inflammatory cytokines in the colon. Juçara supplementation decreased TLR-4 protein content in the colon. Juçara supplementation reducing pro-inflammatory cytokines in EPI. Reduction of TNF-α in EPI is independent of LPS level. Abstract: Obesity is a multifactorial disease with a genesis including the ingestion of hypercaloric diet rich in fat, ultra-processed food, poor in micronutrients and fiber. Some food rich in bioactive compounds are studies to prove their capacity to decrease the deleterious metabolic effect promoted by refined sugar and fat rich-diet. The goal of this study was to evaluate the effect of Juçara ( Euterpe edulis Mart.) supplementation, a fruit rich in fiber and bioactive compounds, mostly anthocyanin, on systemic inflammation in obese mice. Swiss mice were treated with hyperlipidic and hypercaloric diet supplemented or not with 0.5% and 2% of juçara pulp for sixteen weeks. Pro and anti-inflammatory cytokines were evaluated in different tissues. The results showed that sixteen weeks of treatment with hyperlipidic and hypercaloric diet were efficient in developing obesity in mice and juçara supplementation decreased the pro-inflammatory cytokines and TLR-4 protein content in the colon.